Hundreds of TESS Exoplanets Might Be Larger than We Thought - Te Han; Paul Robertson; Timothy D. Brandt; Shubham Kanodia; Caleb Cañas; Avi Shporer; George Ricker; Corey Beard (The Astrophysical Journal Letters, 2025)
The radius of a planet is a fundamental parameter that probes its composition and habitability. Precise radius measurements are typically derived from the fraction of starlight blocked when a planet transits its host star. The wide-field Transiting Exoplanet Survey Satellite (TESS) has discovered hundreds of new exoplanets, but its low angular resolution means that the light from a star hosting a transiting exoplanet can be blended with the light from background stars. If not fully corrected, this extra light can dilute the transit signal and result in a smaller measured planet radius. In a study of hundreds of TESS planet discoveries using deblended light curves from our validated methodology, we show that systematically incorrect planet radii are common in the literature: studies using various public TESS photometry pipelines have underestimated the planet radius by a weighted median of 6.1% ± 0.3%, leading to a ∼20% overestimation of planet density. The widespread presence of these biases in the literature has profoundly shaped—and potentially misrepresented—our understanding of the exoplanet population. Addressing these biases will refine the exoplanet mass–radius relation, reshape our understanding of exoplanet atmospheric and bulk composition, and potentially inform prevailing planet formation theories.